2017
DOI: 10.1051/matecconf/201712002015
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on the building information modeling adoption in United Arab Emirates municipal projects- current status and challenges

Abstract: Abstract. Many modern complex building projects in the public and private sectors are characterized by its poor information management which is manifested by time and cost overruns around the world. Building Information Modelling (BIM) is currently being adopted around the world with various countries mandated its implementation. In specific, the implementation of BIM is rapidly growing in developed countries such as USA, UK, Singapore and Australia, with government mandate through devising strategies and init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Although the UAE takes the lead in BIM adoption and implementation in the Middle East, Mehran (2016) reported that the lack of standards is a main factor in affecting BIM implementation in the UAE construction industry. Similar results peculiar to the UAE have been reported by Venkatachalam (2017). Other research studies that have been reported in the region include the following: Vukovic et al (2015) and Hafeez et al (2016) in Qatar; Skaik and Ali (2013) and Omar and Dulaimi (2015) in UAE; and Matarneh and Hamed (2017) in Jordan.…”
Section: Bim In the Global Construction Industrysupporting
confidence: 78%
“…Although the UAE takes the lead in BIM adoption and implementation in the Middle East, Mehran (2016) reported that the lack of standards is a main factor in affecting BIM implementation in the UAE construction industry. Similar results peculiar to the UAE have been reported by Venkatachalam (2017). Other research studies that have been reported in the region include the following: Vukovic et al (2015) and Hafeez et al (2016) in Qatar; Skaik and Ali (2013) and Omar and Dulaimi (2015) in UAE; and Matarneh and Hamed (2017) in Jordan.…”
Section: Bim In the Global Construction Industrysupporting
confidence: 78%
“…This assertion conforms to the findings by , affirming that the adoption of BIM in a given construction industry contributes to informed decision-making among stakeholders. Similarly, a study by Venkatachalam (2017) concluded that BIM is vital for building complex sustainable infrastructures in the UAE construction industry. However, Venkatachalam (2017) also pointed out that the UAE lags in implementing BIM compared to other developed countries such as the UK and the US where the implementation barriers are the main challenge.…”
Section: Building Information Modelling In the Context Of The Uae Con...mentioning
confidence: 99%
“…The survey also revealed that the perceived BIM use occurs primarily during the design stage. Furthermore, it is noted that while technological preparedness exists in the study environment, people and processes do not [14]. Moreover, District Cooling, which was first used in Dubai in 1999, provides several advantages over traditional cooling systems, including being more ecologically friendly and efficient.…”
Section: Implementationsmentioning
confidence: 99%